The Demand for Quality-adjusted Cash Balances: Price Uncertainty in the U.S. Demand for Money Function - Klein, Benjamin (Journal of Political Economy, 1977)
This paper investigates the importance of uncertainty regarding the rate of rice change as an argument in the long-run money demand function. Increased inflation uncertainty is assumed to lower the stream of monetary services yielded by a given level of real cash balances. The effects on money demand of such changes in the "quality" of money are, in general, theoretically indeterminate. If it is assumed, however, that the monetary service flow is proportional to the real money stock and that the demand for money is interest inelastic, then the predicted relationship between price uncertainty and money demand is unambiguously positive. The empirical findings of this paper, where price uncertainty is operationally measured by the variability of the rate of price change, strongly confirm this positive relationship. These results have important implications for the theory of inflation, the optimum quantity of money, and the potential government tax revenue from money creation.